2016
DOI: 10.1371/journal.pone.0150361
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Characterisation of the Viral Community of Lough Neagh, the Largest Freshwater Lake in Ireland

Abstract: Lough Neagh is the largest and the most economically important lake in Ireland. It is also one of the most nutrient rich amongst the world’s major lakes. In this study, 16S rRNA analysis of total metagenomic DNA from the water column of Lough Neagh has revealed a high proportion of Cyanobacteria and low levels of Actinobacteria, Acidobacteria, Chloroflexi, and Firmicutes. The planktonic virome of Lough Neagh has been sequenced and 2,298,791 2×300 bp Illumina reads analysed. Comparison with previously character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
69
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 64 publications
7
69
1
Order By: Relevance
“…In this geospatial metagenomics study, we identified virome abundance and diversity in different reservoirs and tributaries. Due to insufficient viral genome sequencing information in the NCBI, 41.4% of the virome genome had no significant hits and bacteriophages were the most abundant organisms in the matrix, which is in agreement with previous studies of surface water viromes (Mohiuddin and Schellhorn, 2015;Skvortsov et al, 2016;Tseng et al, 2013). Phages, considered to be the most abundant and diverse biological entities on Earth, play an important role in shaping biological and geochemical processes at the global scale (Díaz-Muñoz and Koskella, 2014).…”
Section: Geospatial Distribution Of Viromesupporting
confidence: 87%
See 1 more Smart Citation
“…In this geospatial metagenomics study, we identified virome abundance and diversity in different reservoirs and tributaries. Due to insufficient viral genome sequencing information in the NCBI, 41.4% of the virome genome had no significant hits and bacteriophages were the most abundant organisms in the matrix, which is in agreement with previous studies of surface water viromes (Mohiuddin and Schellhorn, 2015;Skvortsov et al, 2016;Tseng et al, 2013). Phages, considered to be the most abundant and diverse biological entities on Earth, play an important role in shaping biological and geochemical processes at the global scale (Díaz-Muñoz and Koskella, 2014).…”
Section: Geospatial Distribution Of Viromesupporting
confidence: 87%
“…Determining the factors in constructing the viral community is important for both understanding and manipulating ecosystems (Dinsdale et al, 2008). Factors shaping the viral community in freshwater ecosystems can include temporal factors, geospatial factors, natural disturbances (e.g., typhoon) and human activities (Djikeng et al, 2009;Emerson et al, 2012;Fancello et al, 2013;Ge et al, 2013;Hwang et al, 2017;L opez-Bueno et al, 2009;Skvortsov et al, 2016;Tseng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Elucidating such predominant virus-host interactions is key to characterizing viruses playing central roles in the microbial ecosystem and biogeochemical cycling. However, despite a growing number of viromic studies in freshwater systems (Skvortsov et al, 2016;Moon et al, 2017;Silva et al, 2017;Arkhipova et al, 2018), viruses infecting other typical freshwater bacterioplankton lineages, such as LD12 (Ca. Fonsibacter) (Henson et al, 2018) and Limnohabitans (Kasalický et al, 2013) have yet to be characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Although viral taxa have been continuously updated by the virus research community1011, there are still many misclassifications in the ICTV viral taxonomy12, as well as many viral families currently not included in the RefSeq database. Further, the sequencing of viral metagenomic samples often results in many viral genomes that are of unknown origin1314.…”
mentioning
confidence: 99%